Analisis Faktor Kegagalan Audit Kinerja Pada Audit Sektor Pemerintah - Kukuh Bagus Sajiwo; Arya Tjatur Witjaksono (Journal of Accounting, Finance, Taxation, and Auditing (JAFTA), 2022)
This study aims to determine the influence of what factors can affect failure in performance audit in public sector audits, the method used in this study is a literature study which obtains data through library data and reads, records, and precesses it into research material. The result of this study are factors that fail performance audit, among others: economic and efficiency audits, effectiveness audits and audit failures. The limitation that exists in this study is the limited source of literature study or library data so that the theory used is limited which results in this research not covering widely in terms of discussion to be used in subsequent studies with broad variables.